PERBEDAAN STATUS PEKERJAAN DAN PENYAKIT LANSIA DENGAN DUKUNGAN CAREGIVER DALAM PEMENUHAN AKTIVITAS LANSIA - Nova Yustisia; Titin Aprilatutini; Nurmukaromatis Saleha; Nurkartika Sari (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2022)
Aging can increase the prevalence of non-communicable diseases. Long-term care for the elderly is needed to maintain a level of independence, reduce dependence, prevent disease complications and feel dignified, so as to achieve the quality of life of the elderly. The purpose of this study was to determine the differences in the work and illness of the elderly with the support of a Caregiver in fulfilling activities in the elderly. This research is quantitative research that uses a cross-sectional study design. This study uses a non-probability sampling technique with purposive sampling. The sample of this research is 66 respondents. Analysis of the data used in the form of univariate test and bivariate analysis using the Chi-Square test. The results of the study showed that there was a significant difference between work status and illness in the elderly with caregiver support. The support provided by the caregiver consists of emotional support by providing a safe and comfortable place, information support related to how the elderly should maintain health, instrumental support in fulfilling activities for the elderly, and appreciation support that is needed in fulfilling activities because with the fulfillment of activities the quality of life of the elderly can be improved. to be better.